2017
DOI: 10.1007/s40145-017-0224-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of texture microstructure on tribological properties of tailored Ti3AlC2 ceramic

Abstract: Tribological property of c-axis textured shell-like Ti 3 AlC 2 ceramic was investigated using reciprocating sliding balls (SUS304) under loads of 1, 5, and 9 N. It was found that the textured top surface (TTS), corresponding to the (000l) plane, shows the lowest mean coefficient of friction in comparison with those measured on the textured side surface (TSS), where the sliding directions are parallel (TSS-1) and perpendicular (TSS-2) to c axis, under the same load. Among all the tested orientations, the TSS-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Such strong anisotropic mechanical and tribological properties were expected in MAX phases [9,[29][30][31]. For example, Xu et al reported that textured Ti 3 AlC 2 shows the lowest mean coefficient of friction in the surface corresponding to the (0001) plane [31]. Furthermore, our previous study on Ti 2 AlC-AZ91D reveals that extrusion methods could regulate the orientation of Ti 2 AlC in AZ91D magnesium composites.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Such strong anisotropic mechanical and tribological properties were expected in MAX phases [9,[29][30][31]. For example, Xu et al reported that textured Ti 3 AlC 2 shows the lowest mean coefficient of friction in the surface corresponding to the (0001) plane [31]. Furthermore, our previous study on Ti 2 AlC-AZ91D reveals that extrusion methods could regulate the orientation of Ti 2 AlC in AZ91D magnesium composites.…”
Section: Introductionmentioning
confidence: 75%
“…Hence, we fabricated the composite containing 15 vol.% Ti 2 AlC with semisolid stir casting methods. For comparison, AE44 alloy were also produced; the relative technique details may be found in in our previous publications [31,34]. Briefly, as-cast billets with 60 and 300 mm in diameter and height, respectively, were fabricated through semisolid stir casting under the protection of a mixed SF 6 and CO 2 gas atmosphere.…”
Section: Fabrication Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…where W TAC and W TC are the mass percentage of Ti 3 AlC 2 and TiC, respectively. As shown in Table 2, ρ TAC and ρ TC are the density of Ti 3 AlC 2 (4.25 g/cm 3 ) and TiC (4.93 g/cm 3 ) [29], respectively. The ratio of the measured density to the theoretical density gives the relative density.…”
Section: Effects Of Sintering Temperature and Embedding Powder On Tmentioning
confidence: 99%
“…MAX phases, where M is a transition metal, A is a group A element, and X is either C or N, are a group of intriguing new materials [1]. Titanium aluminum carbide (Ti 3 AlC 2 ), as a member of MAX family, possesses a combination of properties of metals and ceramics [2,3], such as low density (4.25 g/cm 3 ) [4], high electrical conductivity (0.23-0.35 μΩ•m) [5,6], high thermal shock resistance [4,7], low hardness (3.5 GPa) [6], low frictional coefficient [8], good machinability [9], In contrast to the aforementioned methods, pressureless sintering is more attractive for its high shape-forming flexibility and low cost. Li et al [16] firstly reported the PLS of Ti 3 SiC 2 -based compacts from the mechanical alloyed Ti, Si, and C powders after die-pressing at 130-150 MPa and subsequent cold-isostatically pressing (CIP) at 200 MPa.…”
Section: Introductionmentioning
confidence: 99%